Impact of Superovulation for Women with Endometriosis - Kavoussi, Shahryar K. (Seminars in Reproductive Medicine, 2013)
Superovulation (SO)/Intrauterine insemination (IUI) has been used as a treatment approach for endometriosis-associated infertility. The existing medical literature regarding SO in endometriosis patients is composed of heterogeneous studies that differ in terms of study design, SO protocols, the addition of IUI, and comparison groups. There is a need for more well-designed studies to further investigate the efficacy of SO in women with endometriosis-associated infertility. Although in vitro fertilization (IVF) is most effective and is significantly superior to other treatments in endometriosis patients, most of the existing studies suggest some benefit of SO/IUI in infertility patients with early-stage disease. Therefore, SO/IUI is a reasonable early fertility treatment option for women with endometriosis who desire a short trial of potentially more cost-effective treatment options prior to pursuing an IVF cycle and those for whom IVF is not a feasible or desirable option. It appears that gonadotropins are most effective for SO in this patient population even though more head-to-head comparisons are needed.
Keywords: endometriosis; superovulation; infertility; ovulation induction; intrauterine insemination